System of the measures of criminal legal affect in a 20-year practice of the Criminal Code of the Republic of Belarus - Shidlovsky, Andrei V. (Journal of the Belarusian State University. Law, 2019)
The system of the measures of criminal legal affect provided in the Criminal Code of the Republic of Belarus of 1999 is studied in the context of legislative changes during the 20-year practice of its application. The article analyzes the accumulated experience of the national judicial practice in criminal cases and its impact on the transformation of the criminal law policy of Belarus in the implementation of criminal repression. A new gradation in the system of existing measures of criminal law is being purposed. It is based on the conflict criminal legal relations and takes into account the legal nature of their origin, purpose and aims of application. The article develops the theory of differentiation of measures of criminal law impact including restorative, compensatory and material nature.
Keywords: conflict criminal legal relations; criminal legal affect; criminal liability; punishment; sanction; special confiscation; conviction